BIMBINGAN PENYULUHAN ISLAM DALAM MEMBERIKAN MOTIVASI TERHADAP GENERASI STRAWBERY - supriyanto supriyanto supriyanto; Muhamad Rifa’i Muhamad Rifa’i Subhi (Universitas Muhammadiyah Metro, 2023)
One of the aims of this research is to find out how religious counselors play an important role inproviding motivation to the strawberry generation teenagers, especially in providing Islamic education guidance services. One of the methods used in this research is the fielded research method with qualitative descriptive analysis techniques. Data collection for this research was carried out through a literature review from several reference sources, including news, journals and books, using qualitative methods. Apart from that, this research also carried out observations and interviews with various sources, especially religious instructors and teenagers. As we already know, Islamic counseling guidance plays a very important role, not only in dealing with religious issues in providing guidance but also social aspects of society.